Assessment of Cardiovascular Health of Children Ages 6 to 10 Years Conceived by Assisted Reproductive Technology - Cui Linlin; Zhao Min; Zhang Zhirong; Zhou Wei; Lv Jianan; Hu Jingmei; Ma Jinlong; Fang Mei; Yang Lili; Magnussen Costan G; Xi Bo; Chen Zi-Jiang (AMER MEDICAL ASSOC, 2022)
Importance: Assisted reproductive technology (ART) has been widely used for treatment of infertility and has brought millions of births worldwide. The health of offspring conceived by ART has been of much concern, and adverse cardiovascular health outcomes have been reported by previous studies.
Objective: To assess the cardiovascular health of children conceived by ART.
Design, setting, and participants: This cohort study was conducted among participants recruited from November 2017 to February 2019. Participants were 382 children conceived by ART who were selected from a single reproductive center and 382 children who were naturally conceived, randomly selected from a primary school, and matched by sex, age, and maternal age at the child's birth (2 years older or younger). Data were analyzed from March 2019 through December 2019.
Exposures: Conception by ART.
Main outcomes and measures: Blood pressure was measured, and echocardiography was performed to determine left ventricular structural and functional parameters. Adjusted relative wall thickness (aRWT) was found for age, with high RWT defined as an aRWT of 0.375 or more.
Results: Among 764 children aged 6 to 10 years, 382 children were conceived by ART (mean [SD] age, 7.20 [1.21] years; 201 [52.6%] boys) and 382 children were naturally conceived (mean [SD] age, 7.20 [1.21] years; 201 [52.6%] boys). Children conceived by ART had statistically significantly increased mean (SD) height (130.2 [9.5] cm vs 128.5 [8.1] cm; P = .007) and body mass index (17.6 [3.6] vs 17.1 [2.7]; P = .03). Those conceived by ART, compared with children in the matched control group, had statistically significantly increased blood pressure (mean [SD] systolic blood pressure, 105.5 [6.9] mm Hg vs 103.5 [8.4] mm Hg; adjusted P < .001; mean [SD] diastolic blood pressure, 67.2 [5.6] mm Hg vs 62.2 [6.3] mm Hg ; adjusted P < .001), left ventricular systolic dysfunction (mean [SD] left ventricular ejection fraction, 64.61% [3.20%] vs 66.70% [3.89%]; adjusted P < .001), and diastolic dysfunction (mean [SD] early/late mitral/tricuspid diastolic velocities ratio, 1.66 [0.28] vs 2.21 [0.36]; adjusted P < .001). They also had statistically significantly increased parameters of left ventricular structure, including mean (SD) left ventricular mass index (31.97 [5.04] g/m2.7 vs 28.28 [3.54] g/m2.7; adjusted P < .001) and RWT (3.30 [0.41] mm vs 2.98 [0.14] mm; adjusted P < .001). Additionally, children conceived by ART had statistically significantly increased prevalence of left ventricular hypertrophy (9 children [2.4%] vs 2 children [0.5%]; P = .03), high RWT (61 children [16.0%] vs 0 children; P < .001), and left ventricle remodeling patterns, including concentric remodeling (60 children [15.7%] vs 0 children), eccentric hypertrophy (8 children [2.1%] vs 2 children [0.5%]), and concentric hypertrophy (1 child [0.3%] vs 0 children) (P for left ventricle remodeling < .001).
Conclusions and relevance: This study found that children conceived by ART had increased blood pressure and unfavorable changes in left ventricular structure and function compared with children who were naturally conceived. These findings suggest that further studies are needed to investigate the potential mechanisms and long-term outcomes associated with these differences.